Social Capital as a Microlevel Origin of Organizational Capabilities1. Issue 3 (2nd April 2013) - Kemper, Jan; Schilke, Oliver; Brettel, Malte
<x xml:space="preserve">Abstract</x> The microlevel concept of social capital has received significant attention in management and sociological research but has not yet been empirically associated with the development of organizational capabilities. The major purpose of this paper is to investigate the relationship of social capital with marketing and research and development (R&D) capability and to explore how the environmental context moderates the social capital–organizational capability link. It is suggested that top management's social capital provides a firm with important information and control benefits that facilitate effective access to the knowledge and resources necessary for building superior organizational capabilities. In addition, we identify the role of two important environmental factors influencing the social capital–organizational capability link: technological turbulence and competitive intensity. The strength of the relationship between social capital and organizational capabilities is proposed to vary depending on the level of these two environmental characteristics. This study conceptualizes and operationalizes social capital as a multidimensional construct reflected by the structural dimension of tie strength, the relational dimension of trust, and the cognitive dimension of solidarity. Survey and archival data on 280 firms from various industries are analyzed using structural equation modeling. Empirical support for the proposed three‐dimensional structure of social capital is found. Results further indicate that social capital is a significant antecedent to both marketing and R&D capability, which in turn significantly affect firm performance. While a positive relationship between social capital and organizational capabilities is supported in general, the strength of this relationship depends on the environmental context the firm is embedded in. The positive effect of social capital on marketing capability increases in environments with high technological turbulence and competitive intensity; the opposite holds for R&D capability. This research contributes to the resource‐based view by introducing social capital as an important microlevel factor promoting the development of organizational capabilities. By identifying and evaluating two important environmental contingencies, our study also decreases some of the ambiguity surrounding the effectiveness of antecedents to organizational capabilities. The findings further help practitioners decide under what circumstances investing in top‐managers' social capital provides an effective means for achieving superior performance through enhanced organizational capabilities. This should have an important bearing on issues such as management training and incentives as well as on hiring policies.